Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.5194/bg-2021-141
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population dynamics and reproduction strategies of planktonic foraminifera in the open ocean

Abstract: Abstract. It has long been assumed that the population dynamics of planktonic foraminifera is characterised by synchronous reproduction associated with ontogenetic vertical migration. However, due to contradictory observations, this concept became controversial and subsequent studies provided evidence both in favor and against these phenomena. Here we present new observations from replicated vertically resolved profiles of abundance and shell size variation in four species of planktonic foraminifera from the t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Jonkers et al (2015) demonstrated that for some PF species in the Gulf of Mexico, lunar synchronized periodicity in the shell flux was detectable mostly for the larger size fractions. Meilland et al (2021) revealed that more than half of the PF population (of the four studied species) in the tropical Atlantic do not take part in synchronized reproduction. Lin et al (2022) showed that the shell-fluxes of four PF species (>212 µm) were characterized by some degree of lunar periodicity but longer cycles (34-48 days) during three months of peak shell-fluxes in the Northern South China Sea.…”
Section: Pf Timing Of Reproductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Jonkers et al (2015) demonstrated that for some PF species in the Gulf of Mexico, lunar synchronized periodicity in the shell flux was detectable mostly for the larger size fractions. Meilland et al (2021) revealed that more than half of the PF population (of the four studied species) in the tropical Atlantic do not take part in synchronized reproduction. Lin et al (2022) showed that the shell-fluxes of four PF species (>212 µm) were characterized by some degree of lunar periodicity but longer cycles (34-48 days) during three months of peak shell-fluxes in the Northern South China Sea.…”
Section: Pf Timing Of Reproductionmentioning
confidence: 94%
“…The first, is that despite previous suggestions, PF life cycles are not paced by lunar phases, or that the lunar phasing modulation is very minor compared to the impacts of seasonal variations in SST, water column mixing and primary production. Such a case study was demonstrated by Meilland et al (2021) who reported that up to 70% of G. glutinata and G. ruber in the tropical Atlantic do not appear to take part in synchronized reproduction. The second, is that lunar phasing modulation is significantly weaker today relative to several decades ago due to a change in environmental conditions.…”
Section: Pf Flux Patterns and Timing Of Generation Turnovermentioning
confidence: 94%
See 1 more Smart Citation
“…Future studies are needed to constrain the d 11 B spatial distribution in foraminiferal shells caused by potential variations in d 11 B from dissolution, ontogeny (e.g. Meilland et al, 2021) and/or vital effects (e.g. change in photosymbiotic activity throughout the life cycle, Lombard et al, 2009, Henehan et al, 2013, Takagi et al, 2019.…”
Section: Partial Dissolutionmentioning
confidence: 99%